Synthesis of zwitterionic compounds for aquatic toxicity testing for QSAR correlation studies. - Joanna Davies (2003)
22 zwitterionic compounds (10 short-chain surfactants; 12 non-surfactants) were synthesised obeying the general formula R-N+(CH3)2(CH2)nSO3', where n = 2 to 4, by reacting the corresponding N, N-dimethylamines with either sodium-2-chloroethane sulfonate (n = 2), 1, 3- propanesulfonate (n = 3) or 1,4-butanesulfonate (n = 4). The R group varied from a C6 to C12 alkyl chain, to a phenylalkyl unit bearing a Cl to C4 chain and finally to a phenylpropyl unit with a C4 to C6 para-substituted alkyl group. Octanol/water partition coefficients of the 22 sulfobetaines were determined by a conventional stir-flask procedure. The amount of solute in both the octanol and water layer was quantified using a reverse-phase HPLC technique. A UV detection mechanism was employed for those sulfobetaines that possessed a suitable chromophore for UV detection and an electrospray ionisation mode of detection was used for the analysis of those sulfobetaines that lacked a chromophore suitable for UV detection. Acute aquatic toxicity to the aquatic invertebrate, Daphnia magna Straus, was reported as log (l/EC50). The EC50 values were determined experimentally using a standard Acute Immobilisation Test recommended by the OECD Guideline 202 and the internal Unilever document, Ecotoxicology SOP 019 11. A log P-based QS AR was then derived which was found to be analogous to the standard polar narcosis equation, suggesting that zwitterionic sulfobetaines act as polar narcotics. Experimental log P determined by the stir-flask procedure and the rules of Rekker and Roberts for the calculation of log P for quaternary ammonium compounds of the cationic type, were then used in the derivation of key fragment values and interaction factors for use in log P calculations of sulfobetaines using the Leo and Hansch approach. Furthermore, log P predictions provided by KowWin, a computerised program developed by the Syracause Research Cooperation, were suitably amended to take into consideration our experimental results. Finally, an investigation into the suitability of the phospholipophilicity parameter, log k'lAM, for defining aquatic toxicity was performed and the efficacy of using this parameter and log P to predict aquatic toxicity was compared. In addition, other chromatographic methods for estimating log P were investigated. These include the indirect reverse-phase HPLC method, the direct reverse-phase HPLC method and Counter Current Chromatography.